2001
DOI: 10.1002/ddr.1111
|View full text |Cite
|
Sign up to set email alerts
|

Permeability and single‐channel properties of mesenteric, basilar, and septal (coronary) artery smooth‐muscle P2X receptors

Abstract: P2X 1 receptors for ATP are expressed in vascular smooth muscle and are thought to underlie the native artery smooth muscle rapidly desensitising α,β-methylene ATP (α,β-meATP) sensitive P2X receptor phenotype. We have characterised the ionic permeability and single-channel conductance from rat mesenteric, basilar, and septal (coronary) arteries. The relative permeabilities (P X /P Na ) to methylamine, dimethylamine, and Tris were essentially the same for all three arteries and give an estimate of the minimum d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2004
2004
2005
2005

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Although the extrapolation of such data to provide an estimate of pore size needs to be interpreted with caution (as discussed in Ref. 17), it is interesting to note that the estimated minimum pore diameter for schP2X (ϳ0.9 nM) correlates well with that estimated for human P2X 1 and P2X 2 (ϳ0.8 nM) (17,27), suggesting that the ion permeation pathway and selectivity filter are also conserved between these evolutionary remote channels.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Although the extrapolation of such data to provide an estimate of pore size needs to be interpreted with caution (as discussed in Ref. 17), it is interesting to note that the estimated minimum pore diameter for schP2X (ϳ0.9 nM) correlates well with that estimated for human P2X 1 and P2X 2 (ϳ0.8 nM) (17,27), suggesting that the ion permeation pathway and selectivity filter are also conserved between these evolutionary remote channels.…”
Section: Discussionmentioning
confidence: 95%
“…Calcium Permeability-The relative permeability to calcium was determined from the reversal potential of schP2X currents in 112 mM extracellular calcium solution as described previously (17,27). In 112 mM external calcium, currents in response to 100 M ATP were 90 Ϯ 2.7% (p Ͻ 0.01) smaller than the equivalent currents in 154 mM external sodium solution.…”
Section: Potentiation Of Schp2xmentioning
confidence: 99%
“…In arteries P2X 1 receptors do not appear to be randomly distributed throughout the plasma membrane as P2X 1 receptor immunoreactivity appears in clusters (23). This clustering of receptors is supported by electrophysioliogical studies on dissociated artery muscle excised membrane patches; some patches had multiple P2X receptor channels whilst channel activity was absent in others (24). Recent studies also indicate that the P2X 1 receptors can be regulated by phosphorylation of interacting proteins (25) suggesting that the P2X 1 receptor exists in an organised signalling domain.…”
Section: Introductionmentioning
confidence: 83%
“…The association of P2X 1 receptors in lipid rafts may not only be important in maintaining the responsiveness of the receptor but may also be a mechanism to achieve clustering of the receptor. Immunohistochemical and single channel recording studies have indicated that the P2X 1 receptor is not randomly distributed in the membrane but forms clusters (23,24) and that in smooth muscle preparations these clusters are often seen close to sympathetic nerve varicosities; the site of transmitter release. Thus lipid rafts may be a way of concentrating the P2X 1 receptor at signalling hot-spots.…”
Section: Discussionmentioning
confidence: 99%